2009
DOI: 10.1007/s13199-009-0029-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of non-Frankia actinobacteria from root nodules of Alnus glutinosa, Casuarina glauca and Elaeagnus angustifolia

Abstract: Actinobacterial isolates randomly obtained on nitrogen-free BAP medium from surface sterilized root nodules of Alnus glutinosa, Casuarina glauca and Elaeagnus angustifolia sampled from fields were reported. They were assigned on the basis of partial 16S rRNA sequences to Micromonospora, Nocardia and Streptomyces genera. The isolates have been screened for hydrolytic activities, indole acetic acid (IAA) and siderophores production, phosphate solubilization and antagonistic activities. Results suggest putative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…This was demonstrated long back by Fedorov and Kalininskaya (1961) by their ability to grow on N-free medium and acetylene reduction activity. Recent studies using 15 N isotope dilution analysis and identification of nif genes further support this phenomenon (Valdes et al 2005;Ghodhbane-Gtari et al 2010). Molecular studies have established the fact that many actinobacteria can occur as endophytes in various leguminous and non-leguminous plants without forming nodule.…”
Section: Nitrogen Fixationmentioning
confidence: 92%
“…This was demonstrated long back by Fedorov and Kalininskaya (1961) by their ability to grow on N-free medium and acetylene reduction activity. Recent studies using 15 N isotope dilution analysis and identification of nif genes further support this phenomenon (Valdes et al 2005;Ghodhbane-Gtari et al 2010). Molecular studies have established the fact that many actinobacteria can occur as endophytes in various leguminous and non-leguminous plants without forming nodule.…”
Section: Nitrogen Fixationmentioning
confidence: 92%
“…While the ability to grow on nitrogen-free media is used to demonstrate atmospheric nitrogen fixation by bacteria, this line of reasoning may not be true for slowly growing actinobacteria (Ghodhbane- Gtari et al 2010). It is difficult to obtain completely nitrogen-free media that is not contaminated by trace amounts of combined nitrogen in distilled water and other chemical compounds and/or glassware in a routine microbiological laboratory.…”
Section: Conclusion and Prospectivementioning
confidence: 99%
“…In addition, Carro et al (2013) found that Micromonospora strains are ubiquitous in actinorhizal nodules and Micromonospora strains with nitrogenase activity were isolated from nitrogen-fixing root nodules of actinorhizal plants (Niner et al 1996;Valdés et al 2005;Trujillo et al 2006a). This work and others demonstrated the existence in root nodules of non-Frankia symbionts that harbors nitrogenase gene and fix nitrogen (Valdés et al 2005;Gtari et al 2007; Ghodhbane- Gtari et al 2010). Carro et al (2013) stated that Micromonospora isolates are normal occupant of actinorhizal nodules but their function is unknown at the moment.…”
Section: Symbiotic Actinobacteria: Genus Frankiamentioning
confidence: 94%
“…However, the in situ role of endophytic Actinobacteria to the plant life is relative poorly understood although some works reported relationship between their presence and resistance to various biotic and abiotic stress such as light deficiency, diseases (Sessitsch et al 2002), drought (Hasegawa et al 2004) or as PGP that produce IAA (El-Tarabily et al 2009;Ghodhbane-Gtari et al 2010;Nimnoi et al 2010), pteridic acids (Igarashi et al 2002) or indole-3-pyruvic acid (IPYA) (ElTarabily et al (2009). Association of endophytic Actinobacteria with Rhizobiumlegume symbionts was also reported.…”
Section: Endophytic Actinobacteriamentioning
confidence: 99%